Corpus-based and computational approaches to discourse anaphora - Botley, Simon; McEnery, Tony, 1964- (Studies in corpus linguistics ;, 2000)
Discourse anaphora is a challenging linguistic phenomenon that has given rise to research in fields as diverse as linguistics, computational linguistics and cognitive science. Because of the diversity of approaches these fields bring to the anaphora problem, the editors of this volume argue that there needs to be a synthesis, or at least a principled attempt to draw the differing strands of anaphora research together. The selected papers in this volume all contribute to the aim of synthesis and were selected to represent the growing importance of corpus-based and computational approaches to an.